Western Ideas about Elephants - a Commentary - Lyngø, Inger Johanne (Tidsskrift for kulturforskning, 2008)
An elephant is a strange creature. While at home in eastern and southern climatic zones, it also has a rich Western cultural history. This history, or more precisely Western ideas about elephants, is the theme of Nigel Rothfels’s article. The author introduces the reader to an interesting history and not the least rich source material from the presentation of elephants in bestiaries (collections of animal fables) from the Middle Ages through French natural philosopher Comte de Buffon’s Histoire Naturelle (1749-1804) to controversial American photo artist Andres Serrano’s elephant pictures. What kind of elephant do we see in these and other presentations? Which contexts were they part of and what may they tell us today? These are among the questions asked by the author.